Três estrelas do sul global: o fórum social mundial em Mumbai,Nairóbi e Belém - Ana Maria Prestes Rabelo (2011)
Teoric and empiric approach of the global counter-hegemony phenomenon. Taking in account a hegemonic crisis inside the capitalist system and his crises as a social, political and economic order was invastigated the emergence of a field that proposes an alternativecivilizatory grammar. The object of the investigation was the occurrence of three meetings of the World Social Forum, on three continentes in the Global South: Mumbai, in India, Nairobi in Kenya and Belem, in Brazil. It was observed the colonial history of the three countries, thestate formation, the civil society composition and the democratization process. The research was directed to understand how three separate meetings, at times, contexts and different audiencies, kept the core features of the event and deepened the formation of appealing valuesto a new global hegemonic order. The data used to the study was the organizational processes informations of each meeting, registration of participants and of self-organized activities, participant´s profile, semi-structured interviews and participant observation. It was noted thattwo elements give identity and continuity to the meetings: diversity and anti-sistemic agenda (post-colonial and anti-neoliberal). The presence of the two elements in each WSF event was ensured by the developmet level of local social movements, civil society autonomi and statedemocratization. The combination between these factors with the degree of development of global civil society, world situation at the time and coordination with states ruled by sectors commited with the WSF agenda gave better or worse conditions to each event push the globalcounter-hegemony. It was concluded that the WSF is global because it´s capacity to be held in distincts contexts and situations around the world. Also, the WSF internationalize the local struggles and internalize the world struggles. The combination between democractic statesand autonomous civil societys in Global South post-colonial and anti-neoliberal contexts ensures better conditions of occurrence to the WSF and major projection of the counterhegemonic values gathered in it´s interior.